The Role of Aqidah Akhlak (Islamic Creed and Morals) Teachers in Fostering the Religious Character of Junior High School Students through the Scientific Approach - Ghozali Ghozali; Mohammad Asrori; Mokhammad Yahya (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
ENGLISH: The Role of Aqidah Akhlak (Islamic Creed and Morals) Teachers in Fostering the Religious Character of Junior High School Students through the Scientific ApproachObjective: This study aims to analyze the role of Aqidah Akhlak (Islamic Faith and Morals) teachers in strengthening students' religious character through the scientific approach at a junior high school. Methods: This study employed a descriptive qualitative approach. Data were collected through observations, interviews, and documentation. Data credibility was established using source and technique triangulation. Results: The findings indicate that Aqidah Akhlak teachers serve as facilitators, motivators, mentors, supervisors, and role models by integrating religious values into every stage of the scientific approach. Implementation was supported by teacher commitment, a religious school environment, and religious programs, while differences in students' backgrounds, limited parental supervision, and peer influence remained major challenges. Conclusion: Integrating religious values into the scientific approach effectively strengthens students' religious character. Contribution: This study contributes to the development of scientific approach based Aqidah Akhlak learning as a strategy for strengthening religious character in Islamic educational institutions.INDONESIAN: Peran Guru Akidah Akhlak dalam Membentuk Karakter Religius Siswa SMP melalui Pendekatan Saintifik Tujuan: Penelitian ini bertujuan menganalisis peran guru Akidah Akhlak dalam membentuk karakter religius siswa melalui pendekatan saintifik di SMP Al Hamidiyah Sen Asen Konang Bangkalan. Metode: Penelitian menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui observasi, wawancara, dan dokumentasi. Keabsahan data diuji menggunakan triangulasi sumber dan triangulasi teknik. Hasil: Guru Akidah Akhlak berperan sebagai fasilitator, motivator, pembimbing, pengawas, dan teladan dalam mengintegrasikan nilai nilai keagamaan pada setiap tahapan pendekatan saintifik. Keberhasilan didukung oleh komitmen guru, lingkungan sekolah yang religius, dan program keagamaan, sedangkan hambatan meliputi perbedaan latar belakang siswa, kurangnya pengawasan orang tua, dan pengaruh lingkungan pergaulan. Kesimpulan: Integrasi nilai nilai keagamaan melalui pendekatan saintifik efektif membentuk karakter religius siswa. Kontribusi: Penelitian ini memperkaya pengembangan pembelajaran Akidah Akhlak berbasis pendekatan saintifik sebagai strategi penguatan karakter religius di lembaga pendidikan Islam.